Left realism, local crime surveys and policing of racial minorities: a further analysis of data from the first sweep of the Islington Crime Survey - MacLean, Brian (Crime, law and social change, 1993)
The inner-city riots of 1980s Britain provoked an important set of debates in the progressive criminological literature about police accountability and the policing of racial minorities. Two main oppositional political strategies emerged. Following the pioneering work of Hall et al. (1978) some British criminologists supported a police monitoring strategy that proceeded on a case by case approach. In a more generalized approach, the strategy employed by the left realist school made use of the local crime survey in order to gather data on crime and policing practices that were used in public forum to make police accountable. In fulfilling this mandate, the first sweep of the Islington Crime Survey (ICS) provides an empirically grounded analysis of focused military-style policing in the Black community. These authors argue that differential policing practices, such as stop and search patterns, alienate Black youth from the police and contribute to the reduced flow of information from the community to the police vital for police effectiveness at crime control.The premise of this paper is that while both of these positions have been conceptually useful, they probably oversimplify the more complex social response of the Black community to focused policing methods. The paper begins with a critique ofPolicing The Crisis and suggests that it was this critique that primarily motivated the left realist response. In examining the scope of this response, the paper reviews two specific models of these relationships as proposed in various publications from the realist school. It is suggested that seven hypotheses can be deduced from these models, and that data from the first sweep of the ICS allow some assessment of the empirical support for these models.After examining the empirical evidence from the ICS, the paper concludes that while there is considerable empirical support for the analysis provided inThe Islington Crime Survey, the authors have probably not gone as far in their analysis as the data allow. A further analysis suggests that the response to military-style and focused policing, far from being uniform, is, in fact, bifurcated. In some instances, the very people who are the targets of biased policing practices demand more of the same. A model that depicts the complex nature of this response is provided.